PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS KONSUMEN RESTORAN ORIENTAL DI BENGKULU - Yayuk Winarsih; Sularsih Anggarawati (Management Insight: Jurnal Ilmiah Manajemen, 2017)
This research is conducted to analyze the influence of experiential marketing to customer loyalty at sumpit mas restaurant in Bengkulu. The population of the research is the customer of sumpit mas restaurant. The amount of samples are selected 150 costumers by using accidental sampling. The research consists of a dependent variable that is customer loyalty and five independent variables which are dimension of experiential marketing : sense, feel, think, act and relate. Data analysis was carried out quantitatively, using multiple regression analysis with previously tested for validity and reliability. The result showed that sense,feel,think,act and relate towards of the customer loyalty respectively. The result of this research convey that all of the independent variables simultaneously affect the customer loyalty positif and significantly. Partially test proved that all variables affect positif and significant to costumer loyalty where sense variable has affected most significantly. Therefore sumpit mas restaurant should be pay attetion seriously to increase all independent variables to enhance the customer loyalty such as to give cheff sharingpayment system, set the time standar in order taking, serve customer more friendly, hold costumer gathering event at sumpit mas. Management of the companies should improve experiental marketing so in the future customer loyalty more improve and better.